2023
DOI: 10.1039/d2nj05051j
|View full text |Cite
|
Sign up to set email alerts
|

Development of functional cotton fabric by simultaneous dyeing and finishing with a novel bioactive reactive dye

Abstract: Bioactive textiles have garnered considerable attention during the current pandemic COVID-19 owing to their antimicrobial properties. However, the fabrication and utilization of bioactive textiles have imposed a toxic impact on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It can be observed from Fig. 3 that the dye wastewater contains the benzene ring at 296 nm, -SO 3 group at 521 nm and the chromophore in the dye molecule at 543 nm 22 , 23 . The dye’s characteristic wavelength, 545 nm, experienced a rapid decrease due to the UV irradiation.…”
Section: Resultsmentioning
confidence: 95%
“…It can be observed from Fig. 3 that the dye wastewater contains the benzene ring at 296 nm, -SO 3 group at 521 nm and the chromophore in the dye molecule at 543 nm 22 , 23 . The dye’s characteristic wavelength, 545 nm, experienced a rapid decrease due to the UV irradiation.…”
Section: Resultsmentioning
confidence: 95%
“…Comparison of different UV lamps on degradation performanceFigure3displays the UV-visible spectrums of the B-3BF dye wastewater by different UV irradiations with initial Na 2 S 2 O 8 concentration of 15.0 mmol/L at six degradation times, ow rate of 500 L/h, initial pH of 7.8 and initial dye concentration of 20 mg/L. It can be observed from Fig.3that the dye wastewater contains the benzene ring at 296 nm, -SO 3 group at 521 nm and the chromophore in the dye molecule at 543 nm[22][23]. The dye's characteristic wavelength, 545nm, experienced a rapid decrease due to the UV irradiation.…”
mentioning
confidence: 94%
“… 35 A reactive dye based on 1-amino-8-naphthol-3,6-disulfonic acid was developed to impart UV protection to the cotton fabric. 36 Mokhtari et al reported reactive dyes based on N , N -diethyl- m -toluamide (DEET) for imparting mosquito-repellent and antibacterial protection to nylon 6. 37 Singh and Sheikh prepared mosquito-repellent, antibacterial, and UV-protective cotton using the azoic dyeing method by the reaction of Terminalia chebula (a natural dye) and diazotized ethyl anthranilate.…”
Section: Introductionmentioning
confidence: 99%
“…1,4-Diaminoanthraquinone-based UV-protective acid dyes were developed . A reactive dye based on 1-amino-8-naphthol-3,6-disulfonic acid was developed to impart UV protection to the cotton fabric . Mokhtari et al reported reactive dyes based on N , N -diethyl- m -toluamide (DEET) for imparting mosquito-repellent and antibacterial protection to nylon 6 .…”
Section: Introductionmentioning
confidence: 99%